Tindak Kekerasan yang Merupakan Pelanggaran Undang-Undang Perlindungan Anak dan Pemahaman Anak Tentang Bentuk Tindak Kekerasan Terhadap Anak - Dian Ety Mayasari (Universitas Katolik Indonesia Atma Jaya Jakarta, 2016)
Children in their life should be able to grow and develop without violence. Therefore, there needs to be an understanding in the child that violence is a violation of the Child Protection Act. The writer discusses the forms of violence experienced by children, understanding and forms of child protection and children’s understanding of the violence in their life. In order to support this study, using empirical jurisdiction with respondents one hundred and sixty students from 8 private secondary schools in Surabaya. The results showed that the results showed that all respondents had experienced violence in theirlives and the abuser is the closest namely parents. Respondents as children understand about the violence in their life is a violation of the Child Protection Act, but there is no willingness to act to report because the perpetrator most parents are people nearby.